Measurement of bilirubin in cerebrospinal fluid using the oxidase method on automated chemistry system advia XPT - Branzell, Ida; Lillsunde Larsson, Gabriella; Samyn, Dieter; Pettersson-Pablo, Paul (Practical laboratory medicine, 2025)
Evaluate the diagnostic performance of automated, quantitative bilirubin measurement, modified to extend its lower measurement ranges, in cerebrospinal fluid (CSF) using the Siemens analyzer Advia XPT. Results were compared with the gold standard spectrophotometry for diagnosis of subarachnoid haemorrhage (SAH). Eighty clinical samples were analyzed on an Advia XPT, and results were compared to spectrophotometric results using the Agilent Cary 100 bio system. Method performance at low concentrations were evaluated using diluted control material and patient plasma and CSF samples. ROC curve analysis determined a suitable cutoff. Evaluation of low-concentration performance, below 2 μmol/L on Advia XPT, showed a measurement bias of -1.0 %, and a linear regression equation of y = 0.843x + 0.0351 (R2 of 0.975), describing the relationship between measured and expected concentrations of diluted samples. The coefficient of variation, (CV), was 2.92 % at 0.598 μmol/L and 26.6 % at 0.161 μmol/L. Using the outcome of the analysis on Agilent Cary 100 as reference, sensitivity was 100 % and specificity 96 %, employing a cutoff of 0.41 μmol/L. Quantitative measurement of bilirubin in CSF using the bilirubin oxidase method on the automated Advia XPT platform perform well, with the analysis of low concentrations of bilirubin displaying a high precision and a high concordance with the results of spectrophotometry. These preliminary findings are indicative of the merits of quantitative measurement, that warrants further study of its diagnostic potential as an alternative to the more cumbersome spectrophotometry for diagnosing SAH.